Doubling rural farmers’ income through goat farming in India: prospects and potential - Singh, M. K.; Ramachandran, N.; Chauhan, M. S.; Singh, S. K. (Indian Farming, 2018)
Productivity of goats is low (75-100% of their potential) and mortality is high (35-50%) because goats in India (>85%) are kept under sub-optimal production conditions (zero inputs). The net income of majority of goat farmers (with zero-input) ranges from RupeesÂ 2,000 to 3,000/adult female goat/year with an average ofÂ Rupees 2,500. The ratio of profit: cost mostly ranged from 1.5 to 2:1. However, by providing critical inputs, rearing good potential goats, following improved management practices and smart marketing the productivity of goats could be increased by 90 to 160%. The gross income and net income goat/year will increase from RupeesÂ 7,500 toÂ Rupees 10,000 and 5,000 to Rupees 7,500/goat /year, respectively. The expenditure incurred on necessary strategic inputsetc. on one adult female goat and their kids isÂ Rupees 2,500-3,500/year.Thus goat keepers of India may double their income with in one year by adopting improved management practices, low cost innovative technologies and smartly marketing of goat and their products.